Ідентифікація алельних станів гена Rpg1 у сортів ячменю української селекції - Іващук, Б.В.; Пірко, Я.В.; Блюм, Я.Б. (Фактори експериментальної еволюції організмів, 2014)
Aim. Because of providing a valuable resistance to the different pathotypes of stem rust just gene Rpg1 was selected for the molecular analysis. Determination of Rpg1 gene presence and its allelic condition in the Ukrainian barley cultivars were the objectives of this work. Method. Sixty spring Hordeum vulgare variety were chosen for the analysis. The PCR with specific primer were used to distinguish different allele of resistance. Results. Analysis of sixty Ukrainian barley cultivars defined that no one had the Rpg1 gene «resistant» allele. Also, «susceptible» allele was presented only in sixteen cultivars. The pedigree analysis indicates the kinship between the barley samples with the «susceptible» allele. Odesskaya 9 and Odesskaya 115 are the most reliable cultivars of all that could be the origins of «susceptible» allele. But there is no data that these cultivars were crossed with the foreign resistance sources. So it could be another variant of Rpg1 «susceptible» allele that is somehow involved in the signaling plant immunity pathway. Conclusion. Spring barley is a wide grown plant inUkraine and the gradual global climate changes might be a cause of stem rust epidemic emergence in this country. It is necessary that new resistance cultivars of barley are produced in order to avoid future barley harvest loss.